The Relationship Between Internal Factors and Logistics Performance of Logistics Companies in Selangor, Malaysia. - Lim Chia Meng; Wan Nurul Karimah Wan Ahmad (Research in Management of Technology and Business, 2024)
The logistics industry is a crucial driver of economic growth globally, including Malaysia, where it has experienced significant expansion in recent years. In Selangor, specifically the Klang Valley region, has emerged as a prominent logistics hub, it contributing to the state’s GDP and providing employment opportunities. However, the logistics sector faces challenges in maintaining competitiveness and achieving optimal performance, such as intense competition, the need for real-time tracking, supply chain visibility issues and inventory management complexities. The purpose of this research is to determine the relationship between internal factors and logistics performance of logistics companies in Selangor, Malaysia. The population of the research is logistics companies including air, land, sea and rail transportation. The quantitative approach was used in this study through a survey and statistical analysis. The unit of analysis is logistics companies, where the survey respondents would be companies’ executive, manager or supervisor. Therefore, the simple random sampling was used in this study. The result indicate that e-logistics, information technology capability and service quality have a significant relationship with logistics performance, whereas information sharing did not demonstrate a statistically significant relationship with logistics performance of logistics companies in Selangor, Malaysia. In light of these findings, logistics companies in Selangor should focus on implement e-logistics, and invest in information technology and service quality to optimize their logistics performance. This is because continuous monitoring and adaptation to technological advancements will be important for staying competitive and resilient in the ever-evolving logistics sector